Evaluation of Novel Integrated Dielectric Barrier Discharge Plasma as Ozone Generator - Ade Ika Susan; Iis Nurhasanah; Sumariyah Sumariyah; Pratama Jujur Wibawa; Gunawan Gunawan; Anwar Usman; Muhammad Nur; Zaenul Muhlisin; Fajar Arianto; Andi Wibowo Kinandana (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2017)
This paper presents a characterization of an integrated ozone generator constructed by seven of reactors of Dielectric Barrier Discharge Plasma (DBDP). DBDP a has spiral-cylindrical configuration. Silence plasma produced ozone inside the DBDP reactor was generated by AC-HV with voltage up to 25 kV and maximum frequency of 23 kHz. As a source of ozone, dry air was pumped into the generator and controlled by valves system and a flowmeter. We found ozone concentration increased with the applied voltage, but in contrary, the concentration decreased with the flow rate of dry air. It was also found that a maximum concentration was 20 mg/L and ozone capacity of 48 g/h with an input power of 1.4 kW. Moreover, in this generator, IP efficiency of 8.13 g/kWh was obtained at input power 0.45 kW and air flow rate of 9 L/min. Therefore, be the higher ozone capacity can be produced with higher input power; however, it provided lower IP efficiency. The effect of dry air flow rate and applied voltage on ozone concentrations have been studied. At last, spiral wire copper was very corrosive done to the interaction with ozone, and it is necessary to do a research for finding the best metals as an active electrode inside of the quartz dielectric.